Ultraflexible In-Plane Micro-Supercapacitors by Direct Printing of Solution-Processable Electrochemically Exfoliated Graphene - Liu, Zhaoyang; Wu, Zhong-Shuai; Yang, Sheng; Dong, Renhao; Feng, Xinliang; Muellen, Klaus (Advanced Materials, 2016)
A novel direct printing approach for fabrication of in-plane micro-supercapacitors (MSCs) is demonstrated. Solution-processed graphene/conductive-polymer hybrid inks are utilized. The fabricated MSCs on paper substrates offer significant areal capacitance and excellent rate capability. An ultrathin MSC on a poly(ethylene terephthalate) (PET) substrate (2.5 μm thick) exhibits "ultraflexiblity," making it suitable for next-generation flexible microelectrochemical energy-storage devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrochemically exfoliated graphene; energy storage; in-plane; micro-supercapacitors; printing